Moral hazard contracts: does one size fit all? - Alexander K. Koch; Eloïc Peyrache (Institute for the Study of Labor (IZA), 2006)
Incentive theory predicts that contract terms should respond to differences in agents' productivities. Firms' practice of anonymous contracts thus appears puzzling. We show that such a one-size-fits-all approach can be reconciled with standard agency theory if careers are marked by frequent transitions between employers, and agents have career concerns because complete long-term contracts are not feasible.
urn:nbn:de:101:1-2008060610
Keywords: 330